Physiological responses during simulated 16 km recumbent handcycling time trial and determinants of performance in trained handcyclists - Stone, B.; Mason, B. S.; Stephenson, B. T.; Goosey-Tolfrey, V. L. (European Journal of Applied Physiology, 2020)
Purpose: To characterise the physiological profiles of trained handcyclists, during recumbent handcycling, to describe the physiological responses during a 16 km time trial (TT) and to identify the determinants of this TT performance. Methods: Eleven male handcyclists performed a sub-maximal and maximal incremental exercise test in their recumbent handbike, attached to a Cyclus II ergometer. A physiological profile, including peak aerobic power output (POPeak), peak rate of oxygen uptake (VO2Peak), aerobic lactate threshold (AeLT) and PO at 4 mmol/L (PO4), were determined. Participants also completed a 16 km simulated TT using the same experimental set-up. Determinants of TT performance were identified using stepwise multiple linear regression analysis. Results: Mean values of POPeak = 252 ± 9 W, VO2Peak = 3.30 ± 0.36 L/min (47.0 ± 6.8 mL/kg/min), AeLT = 87 ± 13 W and PO4 = 154 ± 14 W were recorded. The TT was completed in 29:21 ± 0:59 min:s at an intensity equivalent to 69 ± 4% POPeak and 87 ± 5% VO2Peak. POPeak (r = - 0.77, P = 0.006), PO4 (r = - 0.77, P = 0.006) and AeLT (r = - 0.68, P = 0.022) were significantly correlated with TT performance. PO4 and POPeak were identified as the best predictors of TT performance (r = 0.89, P < 0.001). Conclusion: POPeak, PO4 and AeLT are important physiological TT performance determinants in trained handcyclists, differentiating between superior and inferior performance, whereas VO2peak was not. The TT took place at an intensity corresponding to 69% POPeak and 87% VO2peak.